The Advantages, Potentials And Safety Of Vtol Suborbital Space Tourism Operations - Zakaria, Norul Ridzuan; Nasrun, Nasri; Abu, Jalaluddin; Jusoh, Asmadi; Azim, Liayana; Said, Md. Azlin; Ishak, Md. Sayuti; Zakaria, Norul Rafidi (2011)

(untitled)
Suborbital space tourism offers short-time zero gravity and Earth view from space to its customers,and a package that can offer the longest duration of zero-gravity and the most exciting Earth view from space to its customer can be considered a better one than the others.